How Do Different Types of Entrepreneurial Networks and Decision-Making Influence the Identification of Entrepreneurial Opportunities? - Yu, Weizhen; Choi, Myeongcheol; Zheng, Jianzhuang (Frontiers in Psychology, 2021)
Entrepreneurial networks are important for entrepreneurial opportunity identification and development in the context of social media. This exploratory research investigates the relationships among entrepreneurial networks, decision-making, and entrepreneurial opportunities, focusing on the role of decision-making in the relationship between entrepreneurial networks and entrepreneurial opportunities. Using data from 512 Chinese entrepreneurial firms, hierarchical regression analyses and structural equation modeling are employed to come up with a mediation model that links entrepreneurial networks to entrepreneurial opportunities through decision-making. Our findings are as follows: (1) heterogeneous networks are positively related to innovative opportunities, whereas homogeneous networks are positively related to imitative opportunities; (2) heterogeneous networks positively affect non-linear decision-making (non-linear DM) while homogeneous networks positively influence linear decision-making (linear DM); (3) positive relationships exist between non-linear DM and innovative opportunities and between linear DM and imitative opportunities; and (4) non-linear DM fully mediates between heterogeneous networks and innovative opportunities, and linear DM partially mediates between homogeneous networks and imitative opportunities. This paper contributes to the entrepreneurship literature by broadening the understanding of the mechanisms of entrepreneurial opportunity formation in emerging markets, and provides important insights for entrepreneurs and policymakers.